Isolation of two triterpenoids from Phlomis purpurea, one of them with anti-oomycete activity against Phytophthora cinnamomi, and insights into its biosynthetic pathway - Fernández-Calleja, L.; García-Domínguez, M.; Redondo, B. Isabel; Martín, J. L. Gómez; Villar, C. J.; Lombó, F. (Frontiers in Plant Science, 2023)
Phytophthora cinnamomi is an important plant pathogen responsible for the dieback diseases in plant genera including Quercus, Fagus, Castanea, Eucalyptus and Pinus, among others, all over the world. P. cinnamomi infection exerts tremendous ecological and economic losses. Several strategies have been developed to combat this pathogenic oomycete, including the search for novel anti-oomycete compounds. In this work, a Mediterranean vascular plant, Phlomis purpurea, has been screened for secondary bioactives against this pathogen. The genus Phlomis includes a group of herbaceous plants and shrubs described as producers of many different bioactive compounds, including several triterpenoids. Triterpenoids are well known molecules synthesized by plants and microorganisms, with potent antioxidant, antitumoral and antimicrobial activities. We have isolated by HPLC-DAD and characterized by HPLC-MS and NMR two nortriterpenoid compounds (phlomispentaol A and phlomispurtetraolone) from the root extracts of P. purpurea. One of them (phlomispentaol A) is active against the plant pathogenic oomycete P. cinnamomi (based on in vitro inhibition bioassays). Based on their chemical structure and their relationship to other plant triterpenoids, oleanolic acid is proposed to be the common precursor for these molecules. The anti-oomycete activity showed by phlomispentaol A represents a promising alternative to counteract the worldwide scale damage caused on forest ecosystems by this pathogen.